Dinâmica da pastagem de sorgo em diferentes ofertas de lâminas foliares e características da carcaça e da carne de vacas de descarte - Osmari, Milene Puntel (2010)
The objective of the present study was to evaluate the sorghum pasture (Sorghum bicolor L. Moench) dynamics under different leaves blades offer, besides cull cows performance and carcass and meat characteristics. Thirty-six animals with average age of 5.5 years and 370 kg of average initial weight was used to forage evaluation. They were kept in 12 sorghum pasture pickets. The treatments used were: 5.1, 7.0, 9.5 and 12.5% of leaf blade offer, where the treatment of 5.1% showed higher accumulation rate (79.24 kg/ha/day of DM) and higher stocking rates (2254.02 kg/ha of weight), besides lesser forage masses (660.53 kg of DM/ha) and principal feet/ha numbers (42000.00 feet/ha). Nevertheless the third experimental period showed lesser accumulation rate (55.70 kg/ha/day of DM), higher forage masses (1986.58 kg/ha of DM) and lesser principal plants and tillers/ha quantities (29000.00 and 41333.33 feet/ha, respectively) in relation to the first and second pasture utilization experimental periods. When the offers and forage age increased, the crude protein levels decreased linearly (P<.05), as much as the sorghum leaves and capim papuã whole plant. In relation to the carcass characteristics, the treatments didn t influence the results (P>.05), with the exception of meat color, that was considered darker in less leaf blade offer treatment (2.5 points), and didn t differing among themselves in other treatments (3.8, 3.6 and 3.6 points, respectively to 7.0, 9.5 and 12.5%).